The Effect of Myofascial Release Technique on Low Back Pain Changes - Sartoyo Sartoyo; Rachma Putri Kasimbara; Achmad Fariz (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Purpose: This study aimed at knowing the clinical efficacies of myofascial release technique to determine the most beneficial result-oriented physiotherapeutic approach for treating pain due to low back pain. Methods: This was a randomized, controlled pretest–posttest experimental study that myofascial release technique. These techniques were compared using a convenience sample of 30 participants with back pain due to muscle spasms with 35-65 age. The numeric pain rating scalewere used to assess the participants’ pain due to back pain, and pain of LBP, at baseline (day 0), day 6, and day 12 post intervention and at during follow-up. All groups were given myofascial releae technique. Repeated-measures ANOVA were used to analyze the data. Results: The within-group analyses showed significant improvement (P0.05) for all variables. Conclusion: MFRT are equally effective for reducing pain with nonspecific low back pain. Furthermore, advice promoting pain reduce can be an adjunct to physiotherapeutic interventions for reducing low back pain and its symptoms. A combination of these manual therapies advice might be a good treatment option for nonspecific pain in physiotherapy clinics